The nature of intrinsic recombination emission in SrSO4 irradiated with ultraviolet photons - Nurakhmetov, T; Tulebayeva, N.; Tolekov, D.A.; Alibay, T.T.; Yussupbekova, B.N.; Sadykova, B.M.; Azmagambetova, Zh.; Daurenbekov, D.H.; Kainarbay, A.Zh.; Zhunusbekov, A. M.; Zhangylyssov, K. B.; Bakhtizin, R. Z.; et al. (Eurasian Journal of Physics and Functional Materials, 2026)
The synthesized SrSO4 crystalline powders were irradiated at photon energies from 6 . 12 eV, in the temperature range from 15 . 300K. The investigationwas carried outbythe methodsof atomic absorp tion, luminescence and vacuum ultraviolet spectroscopy. Intrinsic emissions were found at 3.7-3.8 eV, 4.2-4.6 eV and 4.9-5 eV, and long-wavelength recombination emissions at 2.6-2.7 eV and 2.9-3.0 eV.The synthesized SrSO4 crystalline powders were irradiated at photon energies from 6 . 12 eV, in the tem perature range from 15 . 300K. The investigationwas carried outbythe methodsof atomic absorption, luminescence and vacuum ultraviolet spectroscopy. Intrinsic emissions were found at 3.7-3.8 eV, 4.2-4.6 eV and 4.9-5 eV, and long-wavelength recombination emissions at 2.6-2.7 eV and 2.9-3.0 eV. Recommended Citation Nurakhmetov, T. N.; Salikhodzha, Zh. M.; Bakhtizin, R. Z.; Zhangylyssov, K. B.; Zhunusbekov, A. M.; Kainarbay, A. Zh.; Daurenbekov, D. H.; Azmagambetova, Zh.; Sadykova, B. M.; Yussupbekova, B. N.; Alibay, T. T.; Tolekov, D. A.; Tulebayeva, N.; and Adil, B. (2021) "The nature of intrinsic recombination emission in SrSO4 irradiated with ultraviolet photons," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 2, Article 6. DOI: https://doi.org/10.32523/ejpfm.2021050206